STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENGAKOMODASI GAYA BELAJAR SISWA DI KELAS INKLUSI SEKOLAH DASAR - Rohmah Istikomah (Al-Mudarris: Journal Of Education, 2025)
This study aims to describe the strategies employed by Islamic Religious Education (PAI) teachers to accommodate diverse student learning styles in the Qur’an and Hadith subject within the inclusive classrooms of MIT Ar Roihan Lawang, as well as their impact on learning effectiveness and student participation. Using a descriptive qualitative approach, data were collected through observations, in-depth interviews, and documentation. The findings reveal that PAI teachers implement systematic and responsive teaching strategies tailored to visual, auditory, kinesthetic, and special needs learners. These strategies begin with identifying students’ learning styles, followed by differentiated lesson planning, varied instructional delivery, and flexible assessment. Teachers also work closely with special education support teachers to manage inclusive classrooms effectively. As a result, learning becomes more effective, the students grasp the meaning of verses and hadith more quickly, maintain better focus, and achieve improved learning outcomes. Furthermore, student participation increases significantly; they become more active, confident, and demonstrate positive social interactions in a classroom environment that values diversity. These findings highlight the importance of applying adaptive teaching strategies to create an effective and inclusive learning atmosphere for all students.